1999
DOI: 10.1034/j.1399-3003.1999.13f04.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective pharmacokinetics of S-salbutamol after administration of the racemate in healthy volunteers

Abstract: Racemic R,S-salbutamol is taken to relieve bronchial constriction. Only the R-enantiomer has bronchodilating properties. The S-enantiomer has been proposed to cause in vitro bronchial hyperreactivity in guinea-pigs. Stereoselective elimination of salbutamol has been shown, with S-salbutamol being eliminated at a slower rate than R-salbutamol. This study questioned whether rates of stereoselective elimination were similar after oral or lung delivery, and whether the S:R ratio would increase after repeated inhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…It also seems likely that lung metabolism of inhaled salbutamol may be stereoselective, as suggested by in vitro studies [13] and by the results reported by SCHMEKEL et al [9]. Endotracheal aerosol administration resulted in higher plasma concentration of S-salbutamol but, in the absence of a comparative intravenous study in the same group of patients, it is difficult to quantify pre-systemic metabolism by the lung.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…It also seems likely that lung metabolism of inhaled salbutamol may be stereoselective, as suggested by in vitro studies [13] and by the results reported by SCHMEKEL et al [9]. Endotracheal aerosol administration resulted in higher plasma concentration of S-salbutamol but, in the absence of a comparative intravenous study in the same group of patients, it is difficult to quantify pre-systemic metabolism by the lung.…”
mentioning
confidence: 67%
“…R,S-salbutamol or R,S-fenoterol) has been extensively discussed [5,6], although no firm conclusions have been reached. In animal studies, the administration of racemates and distomers has been shown to enhance bronchial hyperresponsiveness [7,8], but this has not yet been demonstrated in human subjects during chronic dosing.The paper by SCHMEKEL et al [9] in this issue of the Journal contributes to the debate by providing further data related to the pharmacokinetics of salbutamol enantiomers. The results confirm earlier findings [10±12] that an oral dose of R,S-salbutamol is subject to extensive stereoselective first pass metabolism which leads to a high S:R ratio in the plasma, and to exposure to the more slowly cleared distomer in the absence of the eutomer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When R , S -albuterol is given by inhalation, preferential retention of S -albuterol in the lung could lead to increasing concentrations of S -albuterol compared with R -albuterol over time [10]. Moreover, slower metabolism of S -albuterol compared to R -albuterol leads to maximum plasma concentrations and area under the curve of S -albuterol being 2–4 times higher than that of R -albuterol after inhalation of R , S -albuterol [27, 28]. Furthermore, after inhalation of R , S -albuterol, the elimination half-life of S -albuterol is approximately 50% longer than that of R -albuterol [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharmacokinetics of ingested salbutamol was significantly affected by inhaled budesonide in our asthmatic patients. The oral route of salbutamol racemate was deliberately chosen because of higher nominal standard doses and the pronounced disparity in S-and R-plasma levels after ingestion, giving high plasma levels of S-salbutamol (Schmekel et al 1999).…”
Section: Discussionmentioning
confidence: 99%